EVALUASI KOMPETENSI PEDAGOGIK GURU PAI PADA SMA NEGERI SE KOTA PANGKALPINANG (Penerapan Model Evaluasi CIPP) - Yusra Jamali (Universitas Islam Negeri Ar-Raniry, 2018)
The teacher as a profession is personified as a person who is able to transform knowledge well in order to educate the nation's children. This study focuses on evaluating the pedagogic competency of Islamic Religious Education (PAI) teachers in the preparation of learning planning, preparing learning procedures, managing learning and evaluating learning outcomes. This study aims to determine the planning, management, and evaluation of learning. This study uses a qualitative approach with the CIPP evaluation model (context, input, process, and product), while the object of the research is Pangkalpinang City State High School with the subject being the PAI study teacher. Data collection techniques are observation, interviews and documentation studies. The results of the study found that the context (learning planning) of PAI teachers was guided by the education service circular. Inputs (preparation and procedures) are carried out periodically and continuously. Process is carried out by facilitating the development of students' interests and potential. While the product (evaluation of student learning outcomes) is done orally and in direct practice. Whereas (product) evaluation of student learning outcomes is carried out orally and in direct practice. Evaluation of pedagogic competencies of PAI teachers of high schools, carried out by school principals and school supervisors periodically with guided by the education service circular.